การวางแผนกลยุทธ์ทางการตลาดเพื่อเพิ่มความได้เปรียบทางการแข่งขัน ของบริษัท เอส แอนด์ ที คอนเท้มพ์ จำกัด - วรานุภาพกุล, กิตติภพ; ศิริวงศ์, พิทักษ์ (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยเรื่องนี้ เป็นการวิจัยเพื่อหาแนวทางในการพัฒนากลยุทธ์ทางการตลาดของบริษัท เอส แอนด์ ที คอนเท้มพ์ จำกัด เป็นการวิจัยเชิงคุณภาพโดยใช้วิธีการปรากฏการณ์วิทยา โดยเก็บรวบรวมข้อมูลด้วยวิธีการสัมภาษณ์ระดับลึกและ การสังเกตการณ์ ผู้ให้ข้อมูลหลักได้แก่ผู้บริหาร และพนักงานในบริษัท เอส แอนด์ ที คอนเท้มพ์ จำกัด และลูกค้าที่ใช้บริการ ส่วนหนึ่ง การศึกษาครั้งนี้ ได้เก็บรวบรวมข้อมูลโดยใช้ระเบียบวิธีการเก็บหลายวิธีและเครื่องหลายประเภท โดยเน้นการเก็บ ข้อมูลเชิงคุณภาพเป็นหลัก ทั้งนี้ข้อมูลที่ได้จะอยู่ในรูปแบบเอกสารข้อมูลต่าง ๆ ที่เกี่ยวกับ บันทึกงานภาคสนาม เทปบันทึกเสียง ผู้วิจัยได้นำข้อมูลที่ได้มาจัดหมวดหมู่แยกประเภทเพื่อให้ง่ายต่อการวิเคราะห์เนื้อหาและตีความหมาย ผลจากการศึกษา พบทางเลือกแรก กลยุทธ์การเจาะตลาด การสร้างแบรนด์และการสื่อสารการตลาดแบบบูรณาการ เป็นกลยุทธ์ในระยะสั้นและเร่งด่วน เพราะการวางแผนทางธุรกิจ ของบริษัท เอสแอนด์ที คอนเท้มพ์ จำกัด ด้วยกลยุทธ์การเจาะ ตลาด เป้าหมายสำคัญคือการเพิ่มช่องทางการจัดจำหน่ายสินค้าและการให้บริการด้วยความรวดเร็ว เพื่อที่สามารถเข้าถึงกลุ่ม ลูกค้าได้อย่างรวดเร็ว ตลอดจนสามารถแข่งขันกับคู่แข่งขันด้านการเข้าถึงรวดเร็วแก้ไขปัญหาได้ถูกต้อง ทำให้บริษัทต้องเตรียม ความพร้อมด้านต่างๆ ที่เกี่ยวข้อง กลยุทธ์การพัฒนาผลิตภัณฑ์ เป็นกลยุทธ์ระยะกลางเนื่องจากการพัฒนาผลิตภัณฑ์ โดยปกติ บริษัทจะพัฒนา ปรับปรุงตลอดเวลา และจากการวิเคราะห์พบปัญหาเรื่องผลิตภัณฑ์มีผลกระทบในลักษณะไม่เร่งด่วนเท่ากับช่อง ทางการตลาดทำให้กลยุทธ์ดังกล่าวเป็นกลยุทธ์ในระยะกลาง ระยะสุดท้ายคือกลยุทธ์การพัฒนาทรัพยากรมนุษย์นั้น เป็นกลยุทธ์ ระยะยาว เนื่องจากปัญหาที่เกี่ยวข้องกับคนเป็นปัญหาที่ต้องใช้เวลาในการแก้ไข หากแต่ต้องค่อย ๆ ดำเนินการควบคู่กันไป ดังนั้นจึงจัดปัญหาดังกล่าวให้เป็นกลยุทธ์ในระยะยาว Marketing Strategy Planning for Competitive Advantage Enhancement of S&T Contemp Co., Ltd. The research is the study on finding marketing strategy development method of S&T Contemp Co., Ltd. and is the qualitative research by using phenomenology. The data was collected by in-depth interview and observation methods. The major data providers included the executives and the employees of S&T Contemp Co., Ltd., and the customers who used some parts of their services. This study collected the data by utilizing several collection methodologies and service types of equipments and mainly emphasizing on qualitative data collection. Anyhow, the data obtained would be in forms of several data about field site records and recording tape. The researcher classified the obtained data into different categories for ease of content analysis and interpretation. The finding of the results from the study described the first alternative that the strategies of market penetration, brand building, and integrated marketing communications were short-term and urgent strategies due to the business planning of S&T Contempt Co., Ltd. with market penetration strategy. The important target was to increase product distributional channels and rapid services enabling to quickly access the customer targets as well as to compete with their competitors on quick and correct access to problem solving, making the company need different related aspects of preparedness. The product development strategy was medium-term strategy because normally product development would be continuous developed and improved by the company. According to the analysis, the problems found included the effect on products in term of non-urgency being equal to marketing channel making this strategy became the medium-term strategy. The last phase was human resource development strategy which was long-term strategy because human-related problem was the problem that took time to solve but required gradual execution concurrently. This problem management therefore was long-term strategy.